2020
DOI: 10.1016/j.omtm.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Creating New β-Globin-Expressing Lentiviral Vectors by High-Resolution Mapping of Locus Control Region Enhancer Sequences

Abstract: Hematopoietic stem cell gene therapy is a promising approach for treating disorders of the hematopoietic system. Identifying combinations of cis-regulatory elements that do not impede packaging or transduction efficiency when included in lentiviral vectors has proven challenging. In this study, we deploy LV-MPRA (lentiviral vector-based, massively parallel reporter assay), an approach that simultaneously analyzes thousands of synthetic DNA fragments in parallel to identify sequenceintrinsic and lineage-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
0
6
0
1
Order By: Relevance
“…However, we and others have observed that LV titers and infectivity decrease with increasing proviral length, resulting in less efficient transduction of patient cells as well as increased costs for clinical and commercial applications. Optimizing the expression cassette is one strategy to create LVs with optimal titer, infectivity, and expression 5,6 but may be a prolonged process and have to be applied to each individual LV. Improvements of the vector packaging platform or the manufacturing protocol can provide a global solution to the production of many different LVs.…”
Section: Introductionmentioning
confidence: 99%
“…However, we and others have observed that LV titers and infectivity decrease with increasing proviral length, resulting in less efficient transduction of patient cells as well as increased costs for clinical and commercial applications. Optimizing the expression cassette is one strategy to create LVs with optimal titer, infectivity, and expression 5,6 but may be a prolonged process and have to be applied to each individual LV. Improvements of the vector packaging platform or the manufacturing protocol can provide a global solution to the production of many different LVs.…”
Section: Introductionmentioning
confidence: 99%
“…Our rAAV-based approach enabled efficient transduction of the mammalian central nervous system. Our approach differs from recent MPRA strategies which use lentiviral vectors 29,[61][62][63] in that AAV is expressed episomally while lentivirus must first integrate into the genome. Lentivirus is especially useful for in vitro applications with difficult to transfect cell types, as AAV is not very efficient at transducing cell lines 64 .…”
Section: Discussionmentioning
confidence: 99%
“…MPRAs are becoming widely used as an effective tool to assess functionality of cis -regulatory DNA elements in a high-throughput manner ( Ernst et al, 2016 ; Rabani et al, 2017 ; Mattioli et al, 2019 ; Shigaki et al, 2019 ; Choi et al, 2020 ; Davis et al, 2020 ; Ireland et al, 2020 ; King et al, 2020 ; Klein et al, 2020 ; Morgan et al, 2020 ; Renganaath et al, 2020 ). In addition, several modifications to the approach have been described that broaden its applicability ( Rosenberg et al, 2015 ; Shen et al, 2016 ; Safra et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%